Career and technical education program’s influences on post-release outcomes for offenders in Virginia - Kamalludeen, Rosemaliza (2010)
Correctional education’s effectiveness in improving the lives of ex-offenders has been constantly debated. Human capital theory suggests that a person’s income is greatly increased by investments in education and training. Correctional education aims to improve an ex- offender’s life post-release through investment in education. This paper describes post-release employment outcomes and recidivism rates among ex-offenders in Virginia based on their participation in career and technical education (CTE) programs. The aim of the study was to investigate the impact of CTE on time to gain employment post-release, length of employment, and average quarterly earnings among ex-offenders, as well as recidivism. Results revealed better employment outcomes and lower recidivism rates among program participants, suggesting positive influences of correctional education on post-release outcomes among ex-offenders. Further investigation is suggested to include demographics and other variables as they might have direct or indirect effects on ex-offenders’ employment outcomes and recidivism likelihood.